A Case of Atopic Myelitis with Cervical Cavernous Angioma - Miyuki Fukuda; Hiroaki Manabe; Nobuhiro Sasaki; Masayuki Kuroda; Minoru Hoshimaru; Shigeo Ueda (Case Reports in Medicine)
Atopic myelitis, a type of myelitis which appears in patients with elevated serum levels of immunoglobulin E (IgE), occurs more commonly in the cervical spinal cord, but this mechanism has not yet been elucidated. Herein, we experienced a case of atopic myelitis developed during the growth of cervical cavernous angioma caused by bleeding. A 37-year-old woman suffered from hand swelling caused by a house cat licking. At the same time when cavernous angioma had grown, she experienced a numbness in her four extremities, and multifocal peritumoral hyperintense spinal cord signals were seen. The diagnosis of atopic myelitis was made because we observed significantly elevated levels of specific IgE antibody to cat dander. Symptoms disappeared immediately after steroid pulse therapy. We subsequently resected a cavernous angioma, and eosinophil invasion was found inside it. This is the first case report of atopic myelitis which developed in association with spinal cord vascular lesions. A local blood-brain barrier breakdown due to hemorrhagic lesions of the spinal cord may have contributed to the onset of atopic myelitis.